Pengaruh Substitusi Tepung Daun Stevia (Stevia Rebaudiana) Terhadap Kadar Gula Reduksi Dan Tingkat Kekerasan Biskuit Ubi Jalar Ungu(Ipomoea batatas L.) - Mayanningtyas, Yassenda, Endang Nur W., SST., M.Si. Med, Fitriana Mustikaningrum, S.Gz., M.Sc (2017)
Background: Diabetes mellitus (DM) is one of the biggest health problem in the world, including Indonesia. One way to control it is through diet management to maintain blood sugar levels and provide enough energy. Foodstuffs, such as purple sweet potato and stevia leaf can be used as raw material of biscuits for diabetic patient. Sweet potato has a low glycemic index, as much as 48, and is a good source of carbohydrates for diabetics. Furthermore, stevia leaves can be used as an alternative in the manufacture of low-calorie natural sugar. Purpose: The purpose of the research was to evaluate the effect of stevia leaf (Stevia rebaudiana) flour substitution on reducing sugar and hardness of purple sweet potato (Ipomoea batatas L.) biscuit. Method: Completely randomized design was used with 4 treatments substitution of stevia leaf flour, were 0 g; 1,35 g; 2,70 g and 4,05 g. Nelson-Somogyi was used to analyze the reducing sugar of biscuit. Data were anayzed using one way ANOVA, with a significant level of 95%, and followed by Duncan's Multiple Range Test (DMRT). Result: The highest of reducing sugar, as much as 8,85%, indicated by biscuit substitututed with stevia leaf flour 1,35 g. The lowest recuding sugar, however, has been given by substitution of stevia leaf flour 4,05 g (6,89%). The hardness of biscuit was at a range of 3714,5 g until 4282.5 g. Conclusion: There is an effect of stevia leaf flour substitution on reducing sugar of biscuit. However, the hardness of biscuit is not affected by subtitution of stevia leaf flour. Suggestion: Need to do research on chemical properties and nutritional value of purple sweet potato biscuits substituted stevia leaf powder.